Codex Bezae : studies from the Lunel colloquium, June 1994 - Parker, D. C.; Amphoux, Christian-Bernard. (New Testament tools and studies, 1996)
A group of biblical and patristic scholars and palaeographers met in Lunel, Herault, in June 1995 to discuss the many questions posed by Codex Bezae to our understanding of the use of the Gospels and Acts in early Christianity, and of the text of the New Testament. This collection makes the papers and debates of the colloquium available for a wider discussion. The papers cover two broad areas. The first addresses palaeographical questions. The second covers textual matters, subdivided between the Gospels and Acts. The 24 contributors include J.N. Birdsall, J. Irigoin, L. Holtz, B.D. Ehrman, M.W. Holmes, J.K. Elliott, J.M. Auwers and M.-É. Boismard. There is an introduction by the editors, who also provide analyses of each main section. The range of interests represented by the participants and by the papers has already stimulated fresh developments.